Problematika Penulisan Mushaf Al-Qur’an Berdasarkan Analisis Netnografi dalam “Muslim Pro Apps Versi Tahun 2020-2025“ - Ahmad Fathurrobbani; Samani Samani; Nasirul Islam Kholilulloh (Fakultas Agama Islam Universitas Darul 'Ulum Jombang, 2026)
ABSTRACT This research explores the problems in the writing of the Qur’anic manuscript within the Muslim Pro application (2020–2025 version) using a netnographic analysis. The background of this study lies in the increasing use of digital mushaf, which raises concerns about textual accuracy, consistency of rasm, and completeness of diacritical marks. The purpose of this research is to identify errors in Qur’anic writing and to understand users’ responses to these issues. The method applied is qualitative with a netnographic approach, analyzing data from user reviews and comments on digital platforms related to Muslim Pro. The findings reveal several problems, including technical errors in letters and diacritics, inconsistencies with rasm Uthmani, and differing user perceptions regarding digital mushaf standards.This study concludes that the problems in mushaf writing are not only technical but also connected to religious sensitivity. Therefore, the involvement of Qur’anic scholars in digital verification is essential to ensure the authenticity and reliability of digital mushaf. Keywords: Qur’anic manuscript, Problems, Netnography, Muslim Pro